Research Careers: Some Reflections from Europe - Teichler, Ulrich; Schomburg, Harald (International Higher Education, 2008)
Considerable attention is paid across Europe to the formative years of scholarsthe career period between graduation from a university and the eventual appointment to a senior supervisory position at a higher education or research institution. A study on academic careers in a number of European countries shows that employment conditions and career patterns for young academics vary substantially by country. However, short-term employment until about the age of 40 and high levels of selectivity are common in many countries.